2022
DOI: 10.1016/j.pmn.2021.09.001
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of a Fibromyalgia Online Nursing Consultation in the Quality of Life: A Randomized Controlled Trial

Abstract: Background: Aim: To evaluate the effectiveness of an online nursing consultation through the Internet platform Red Sinapsis (RS) in improving the perceived quality of life of patients with fibromyalgia (FM). Method: Eighty patients with FM were randomized to an intervention group (n = 40) or control group (n = 40). The intervention group (IG) was monitored by a nursing specialist through the online platform RS while the control group (CG) received standard follow-up at the clinic. The Fibromyalgia Impact Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Table 2 summarizes the detailed protocols of telerehabilitation among the included studies. Regarding the medium of telerehabilitation, 8 studies used internet-based telerehabilitation [ 20 , 28 , 29 , 31 - 33 , 35 , 36 ], 5 used telephone- or mobile app–based telerehabilitation [ 18 , 21 , 27 , 30 , 34 ], and 1 used a wearable device to monitor and record real-time pain [ 19 ]. In terms of telerehabilitation programs, 6 studies used psychological interventions–based telerehabilitation [ 20 , 27 , 29 , 30 , 32 , 33 ], 2 used fibromyalgia self-management–based telerehabilitation [ 21 , 28 ], 3 used video-based guided exercise training telerehabilitation [ 18 , 35 , 36 ], 1 used a web-based pain course–based telerehabilitation [ 31 ], 1 provided real-time pain monitoring by a monitoring system [ 19 ], and 1 study provided web-based teleconsultation [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 2 summarizes the detailed protocols of telerehabilitation among the included studies. Regarding the medium of telerehabilitation, 8 studies used internet-based telerehabilitation [ 20 , 28 , 29 , 31 - 33 , 35 , 36 ], 5 used telephone- or mobile app–based telerehabilitation [ 18 , 21 , 27 , 30 , 34 ], and 1 used a wearable device to monitor and record real-time pain [ 19 ]. In terms of telerehabilitation programs, 6 studies used psychological interventions–based telerehabilitation [ 20 , 27 , 29 , 30 , 32 , 33 ], 2 used fibromyalgia self-management–based telerehabilitation [ 21 , 28 ], 3 used video-based guided exercise training telerehabilitation [ 18 , 35 , 36 ], 1 used a web-based pain course–based telerehabilitation [ 31 ], 1 provided real-time pain monitoring by a monitoring system [ 19 ], and 1 study provided web-based teleconsultation [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies with 764 participants assessed QoL. The QoL was assessed using the Short Form Health Survey in 5 studies [ 28 , 31 , 34 - 36 ] and the EQ-5D in 1 study [ 19 ]. In these studies, we found no significant heterogeneity in the QoL ( I 2 =0%; P =.56).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations